2016
DOI: 10.1080/10409289.2016.1246288
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Teacher–Child Relationships: Links With Children’s Observed Interactions

Abstract: Research Findings: The present study examined associations between children's classroom interactions and teachers' perceptions of teacher-child relationships during 1 year of preschool. Teachers (n = 223) reported their perceptions of closeness and conflict in their teacher-child relationships in the fall and spring. Children's (n = 895) positive classroom interactions with teachers, peers, and learning activities and their negative interactions were observed midyear. Children's positive interactions with teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 62 publications
(108 reference statements)
0
21
2
3
Order By: Relevance
“…Moreover, the inCLASS captured individual differences between kindergarten students in the four domains. However, in three of the four inCLASS domains, including Teacher Interactions, Peer Interactions, and Task Orientation, standard deviations were about a third to half as large as those in other studies (e.g., Downer et al, 2010;Hartz et al, 2017), whereas limited variability and skewness that we observed for Negative Engagement matched other work (e.g., Downer et al, 2010;Vitiello et al, 2012). It should be noted, however, that the alphas for each domain in our study were lower than in other work, so comparisons should be considered with this in mind.…”
Section: The Inclass Among Low-income Kindergarteners: Comparison Witcontrasting
confidence: 60%
See 1 more Smart Citation
“…Moreover, the inCLASS captured individual differences between kindergarten students in the four domains. However, in three of the four inCLASS domains, including Teacher Interactions, Peer Interactions, and Task Orientation, standard deviations were about a third to half as large as those in other studies (e.g., Downer et al, 2010;Hartz et al, 2017), whereas limited variability and skewness that we observed for Negative Engagement matched other work (e.g., Downer et al, 2010;Vitiello et al, 2012). It should be noted, however, that the alphas for each domain in our study were lower than in other work, so comparisons should be considered with this in mind.…”
Section: The Inclass Among Low-income Kindergarteners: Comparison Witcontrasting
confidence: 60%
“…Furthermore, low-income educational settings, which disproportionately serve children of color, tend to be relatively more rigid and to be characterized by, on average, lower quality learning and interaction opportunities compared with more sociodemographically advantaged settings (Duncan & Murnane, 2014). Thus, extending existing work on the inCLASS Hartz, Williford, & Koomen, 2017;Slot & Bleses, 2018;Vitiello, Booren, Downer, & Williford, 2012), the present study investigates (a) the measure's applicability in a high-poverty, mostly African American kindergarten sample; (b) associations between inCLASS and teacher reports of children's social skills and learning behaviors; and (c) characteristics at the time point, child, and classroom levels that contribute to inCLASS scores.…”
mentioning
confidence: 99%
“…Using teacher report to measure both relationship quality and classroom behaviour leads to a problem with shared method variance (Sabol and Pianta , Hartz et al . ). A limitation of our study is that we do not include multiple informants of relationship quality and children's behaviour.…”
Section: Discussionmentioning
confidence: 97%
“…Only program components related to social, emotional, behavioral, and/or relational development were included. This was determined because social, emotional, behavioral, and relational development can affect interactions between teachers and students (e.g., Conroy et al, 2015), and positive STIs can affect the STR (Hartz et al, 2017). In addition, similar practices were combined to create practice elements.…”
Section: Methodsmentioning
confidence: 99%